Pilot Study of Digital Competency Mapping of Indonesian Preservice Teachers: Rasch Model Analysis - Muhammad Luthfi Hidayat; Shemsu Gulta Abdurahman; Dwi Setyo Astuti; Ratna Prabawati; Sofyan Anif; Hariyatmi Hariyatmi; Fathul Zannah (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
Typically, biology students pursue natural sciences. As the world becomes increasingly interconnected and reliant on digital technologies and platforms, it is essential to evaluate their technological preparedness. This study aims to validate a mapping instrument of the digital competence of pre-service Biology teachers in a leading private university in Indonesia. The analysis used the Rasch model to measure the validity and reliability of questionnaire instrument utilizing the Logit Value of Item (LVI). The Digital competency (Digcom) questionnaire contains 36 statements in the Indonesian language (Bahasa). This questionnaire aims to record respondents' answers to digital skills for preservice teachers. The statement is adapted from the digital competence area for EU citizens combined with the Digital Literacy guidelines of the Indonesian Ministry of Communication and Information. The result of the retranslation has been validated to remove the ambiguity of each item of the statement by English language experts. The pilot research was conducted on preservice teachers from different backgrounds (gender, department, and year of study) in a private University (n=261). The findings indicated that all the items were deemed acceptable as they met the criteria for the PTMEA-CORR range, MNSQ outfit, and ZSTD outfit. This study is among the few that have explored the digital competency framework of preservice teacher students in Indonesia, specifically in relation to the difficulty level of each competency area.